Factors Associated with Treatment Duration in a Trauma-Focused Community Mental Health Setting - Jason Fly; Erika Felix; Bita Ghafoori (Behavioral Sciences)
Using the behavioral model of engagement in health services, the current study assessed client characteristics that may contribute to treatment duration in trauma-focused psychotherapy in a community clinic setting. Participants (n = 893) were adults ages 18–78 years old (M = 36.36, SD 12.37). Demographic data (e.g., age, income) and health profile questionnaires assessing trauma and depression symptoms were collected at intake and every three sessions thereafter to track health outcome progress. Logistic regression models assessed factors associated with treatment duration at three time points: treatment initiation (0–2 sessions), treatment engagement (3–5 sessions), and treatment sustainment (6–8 sessions). For this sample, 38.6% ended treatment at the treatment initiation phase. Lower education level and higher quality of social relationships was predictive of ending treatment. In the engagement phase, 29.2% of the remaining participants (n = 548) ended treatment before six sessions, but there were no predictors of ending. During the sustainment phase, 31.7% ended treatment. African American race was associated with ending at this phase. In total, 70.3% of participants ended treatment before nine sessions. Participants who remained in treatment through the sustainment phase showed significant improvement in trauma and depression symptoms at each of the previous treatment phases, providing evidence of a dose response effect. Lower education, higher quality of social relationships, and African American race were associated with leaving treatment early. Many participants ended treatment before nine sessions, but those that completed treatment experienced improvement in symptoms to sub-clinical levels.